Lubricant operation plastic and semifluid lubrication - Мнацаканов, Р. Г.; Довбуш, В. О.; Якобчук, О. Є.; Микосянчик, О. О. (Proceedings of National Aviation University (archive), 2021)
In operation the trials plastic and semi-fluid of lubricant oils are carried out and the change tribotechnical characteristics is submitted, the change of width of a lubricant stratum, friction torque and rotational speed is analysed during an operating time for lubricant oils, which were tested.